Testing soil phosphorus in a depleting P scenario: an accelerated soil mining experiment. (12th July 2018) - Nawara, S.; van Dael, T.; De Cooman, E.; Elsen, A.; Merckx, R.; Smolders, E.; Amery, F.
Summary: The reduced use of phosphorus (P) fertilizer in fertile soil has reverted the P balance to negative in some regions. It is unclear how long current soil P stocks will ensure adequate P supply to crops. In addition, it is unknown if current soil tests for available P describe bioavailable P adequately in soil where P is becoming depleted. We set up an accelerated soil P mining test to address these questions. Perennial ryegrass ( Lolium perenne, Melpetra tetra) was grown for 2 years in a greenhouse on 5‐cm‐deep soil layers of eight contrasting soils with periodic grass clipping. Each soil was split into four fertilizer treatments (i.e. no P (–P) and adequate P (+P)) and two nitrogen levels, the latter to alter the rate of P uptake. The long‐term P mining induced P‐related yield losses in seven of the 16 soil treatments. The cumulative uptake of shoot P at which yield loss started to exceed 10% (–P versus +P) varied over a small range of 37–74 mg P kg −1 soil among the soils. This critical cumulative P uptake (CCP) was related to the soil P content prior to mining measured by five soil P tests (ammonium oxalate, ammonium lactate (AL), Olsen P, 0.01 m CaCl2 and the diffusive gradient in thin film technique (DGT)); the largest R 2 values were observed for P‐AL ( R 2 = 0.72) and P‐DGT ( R 2 = 0.73). However, none of the tests was diagnostic for yield loss during the depletion period. Increased N supply accelerated growth and rates of P uptake and decreased the CCP by a factor of 1.7 on average, illustrating the effect of the rate of biomass production. The CCP values obtained in the treatment with reduced N fertilizer application are likely to be the most relevant for the field and suggest that current stocks allow adequate P supply for arable crops for 3–8 years under zero P application (0–23 cm) in soils similar to those tested. The lack of a successful diagnosis for P deficiency during this depletion experiment calls for further calibration of soil tests for available P in the field. Highlights: The availability of legacy P in well‐fertilized soil was evaluated with a P mining pot trial 10% loss of crop growth occurred when soil P was depleted by 37–74 mg P kg −1 soil Accelerated plant growth with increased N supply decreased total P uptake beyond which P deficiency occurs In a depletion scenario, current soil P tests are not diagnostic but they can be used for prediction